The significance of polymorphism and expression of oestrogen metabolism-related genes in Chinese women with premature ovarian insufficiency. Issue 5 (November 2017) - Qin, Chunrong; Chen, Yong; Lin, Qing; Yao, Jilong; Wu, Weiqing; Xie, Jiansheng
Abstract: The aim of this study was to investigate whether polymorphism and expression of CYP17, CYP1A1, COMT and SULT1A1 affected the risk of idiopathic primary ovarian insufficiency (POI) in Chinese women. DNA sequencing and real-time PCR were used to detect these genes in 132 cases of idiopathic POI and 132 normal women. A significant increase in the C allele of CYP17 (rs743572) polymorphism was observed in women with POI compared with controls (PFDR = 0.046). A significant decrease was observed in the C allele of CYP1A1 (rs4646903) in women with POI compared with controls (PFDR = 0.004). The A allele of COMT (rs4680) polymorphism was more frequent in women with POI compared with controls (PFDR = 0.029). The genotypic frequency of SULT1A1 (rs9282861) was not significantly different between the two groups. For the relative expression of CYP17 and COMT were statistically significant (both PFDR = 0.066), with false discovery rate controlled at 0.1. No significant difference was observed in the RNA levels of CYP1A1 and SULT1A1 between the two groups. The frequency of expression of the CYP17 T/C variant tended to be higher and the A allele of COMT polymorphism together with down-regulation of its mRNA expression may be more frequent in Chinese women with idiopathic POI.